PERANCANGAN PROGRAM BERKELANJUTAN NAGARI MEMBANGUN DI NAGARI GANTING MUDIK SELATAN SURANTIH KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Yeffi Masnarivan; Obel Obel; Yoko Masna Rivan M; Esthika Ariany Maisa (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Currently, Nagari Ganting Mudik South Surantih is still in the category of underdeveloped villages. Three main issues in the nagari will try to be offered for assistance, namely in health, education, and village governance. The activity aims to design a program to assist the nagari to build in Nagari Ganting Mudik South Surantih, Sutera District, South Pesisir Regency. The method of implementing the activity is to hold direct meetings in consultations on a plan for the next three years between the proposer team and the nagari government, such as Walinagari and their apparatus, Bamus, Youth, PKK, and community leaders. The results obtained were that three problem areas were identified as problems in Nagari Ganting Mudik South Surantih, namely the fields of health, education, and village governance. The solutions planned in the health sector are 1) handling malnutrition and stunting, 2) activating family planning villages, 3) increasing community participation in participating/getting health insurance, 4) handling chronic energy deficiency events (KEK) experienced by pregnant women, 5) increase the percentage of people who have proper latrines. Solutions in the field of education are 1) handling children who drop out of school, 2) realizing the community's needs who want to get packages A, B, and C, 3) innovative education in the use of social media. The solutions in nagari governance are 1) training the nagari apparatus that manages the website and completes the data, and improves the appearance of the website, and 2) trains the nagari apparatus in making letters and filing them. This activity concludes that it has been mutually agreed between the service team and partners to carry out activities on the designs that have been prepared together for the next 1-3 years, as evidenced by the signing of cooperation (MoU).